Implementation of Resistance Band Training to Increase Reaction Time for Straight Punches Based on the HITensor Kick Shield Pad Technology - Ajid, Oktoviana Nur; Febrianty, Mona Fiametta (Universitas Pendidikan Ganesha, 2023)
In martial arts sports, the elements that are often measured in sports performance are punches and kicks. The purpose of this study was to determine the effect of resistance band training on the reaction time of straight punches as well as to identify the accuracy of the newly developed speed measuring instrument, namely the hitsensor kick shield pad, the shape of the measuring instrument attached to the pecing pad resembles a target so that the movement can be adjusted to the attack movement, during the match. This research uses an Experimental Approach to the Problem, using a test and retest design research design. The sample consisted of 8 people (range: age, 19-23 years; height, 165-180 cm; mass, 45-90 kg). The instrument in this research was a straight punch test using the Hitsensor Kick Shield Pad technology tool. The data analysis technique uses the paired t-test. This test is used to find out whether there is a difference in the average of two paired samples. The result is that there is an effect of training using resistance bands on increasing the reaction of straight punches of pencak silat athletes using a Hitsensor technology measuring instrument that resembles a real target.